A Matter of V A Matter of Value: Cr alue: Creative Writing Str riting Strategies and Their ategies and Their Transference to Composition o Composition - Brandy Dawn Clark (Missouri State University, 2023)
Creative writing and composition seem to be taken, at least in the academic world, as separate and unequal entities. While there are many questions in the research and answers in the research as to why creativity is important, its practical application in the composition classroom is not readily discussed because there is not unanimous agreement as to if creative writing even belongs in the composition classroom. Practical application of creative writing in the composition classroom gives teachers the opportunity to see why it is important, to see why it is valuable, and to incorporate it into already meticulous class standards. Using the data from a survey on what creative writing revision strategies students find helpful to use in their other courses, I designed a unit plan for a first-year composition class that incorporates both a creative writing assignment and these revision strategies typically learned in a creative writing class. I wish to show that while composition strategies are important in the creative writing classroom, that the opposite is also true: creative writing and creative writing strategies are important in the composition classroom